Hydrodynamic Cavitation-Assisted Synthesis of Nanocalcite - Shirish H. Sonawane; Sarang P. Gumfekar; Kunal H. Kate; Satish P. Meshram; Kshitij J. Kunte; Laxminarayan Ramjee; Candrashekhar M. Mahajan; Madan G. Parande; Muthupandian Ashokkumar (International Journal of Chemical Engineering)
A systematic study was made on the synthesis of nanocalcite using a hydrodynamic cavitation reactor. The effects of various parameters such as diameter and geometry of orifice, CO2 flow rate, and Ca(OH)2 concentration were investigated. It was observed that the orifice diameter and its geometry had significant effect on the carbonation process. The reaction rate was significantly faster than that observed in a conventional carbonation process. The particle size was significantly affected by the reactor geometry. The results showed that an orifice with 5 holes of 1 mm size resulted in the particle size reduction to 37 nm. The experimental investigation reveals that hydrodynamic cavitation may be more energy efficient.